Experiences of Indonesian nurses as Hajj health personnel in caring for Hajj pilgrims: A qualitative study - Sugeng Sugeng; Sri Setiyarini; Probosuseno Probosuseno; Nyoman Kertia (Belitung Nursing Journal, 2024)
Background: Investigating the experiences and roles of nurses during Hajj is vital due to the unique public health challenges posed by the mass gathering of diverse pilgrims. Nurses play a crucial role in disease surveillance, infection control, and managing emergencies like heat stroke and injuries. Their insights can improve emergency preparedness and public health management.